Patient and general practitioner experiences of implementing a medication review intervention in older people with multimorbidity: Process evaluation of the SPPiRE trial - Caroline McCarthy; Ivana Pericin; Susan M. Smith; Bridget Kiely; Frank Moriarty; Emma Wallace; Barbara Clyne (Wiley, 2022)
Abstract Introduction The SPPiRE cluster randomized controlled trial found that a general practitioner (GP)‐delivered medication review that incorporated screening for potentially inappropriate prescriptions (PIP), a brown bag review and a patient priority assessment, resulted in a significant but small reduction in the number of medicines and no significant reduction in PIP. This process evaluation aims to explore the experiences of GPs and patients and the potential for system‐wide implementation. Methods The trial included 51 general practices and 404 participants with multimorbidity aged ≥65 years, prescribed ≥15 medicines. The process evaluation used mixed methods and ran parallel to the trial. Quantitative data was collected from the SPPiRE intervention website and analysed descriptively. Qualitative data on medication changes were collected from intervention GPs (18/26) and a purposive sample of intervention patients (27/208) via semi‐structured telephone interviews. All interviews were transcribed verbatim and analysed using a thematic analysis. Qualitative and quantitative data were integrated using a triangulation protocol. Results The analysis generated two themes, intervention implementation and mechanisms of action, and both were underpinned by the theme of context. Intervention delivery varied among practices and 45 patients (28%) had no review, primarily due to insufficient GP time. 80% of reviewed patients had ≥1 PIP identified, 59% had ≥1 problem identified during the brown bag review and 79% had ≥1 priority recorded. The brown bag review resulted in the most deprescription of medications. GPs and patients responded positively to the intervention but most GPs did not engage with the patient priority‐setting process. GPs identified a lack of integration into practice software and resources as barriers to future implementation. Conclusion The SPPiRE intervention had a small effect in reducing the number of medicines and this was primarily mediated through the brown bag review. The context of resource shortages and deep‐seated views around medical decision‐making influenced intervention implementation. Patient or Public Contribution Qualitative data on the implementation of the medication review and their wider views on their medicines was collected from older people with multimorbidity through semi‐structured telephone interviews. Clinical Trial Registration The SPPiRE trial was registered prospectively on the ISRCTN registry (ISRCTN12752680).